Implementasi E-Raport Dalam Mengelola Penilaian Sumatif Untuk Meningkatkan Hasil Belajar Siswa - Kirmadi, Yudi; Iskandar, Yogi; Muhtadin, Muhtadin; Subandi, Ika; Finorita, Eny Tantia; Ningsih, Syafitri; Wasitoh, Evi; Ismaya, Bambang; Suryaman, Maman (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The background to this community service activity is that reporting learning outcomes at SMA Negeri 2 Karawang still faces obstacles due to the manual input process of grades, which is time-consuming and prone to errors. This condition hinders the effectiveness of academic administration and the achievement of digital-based education services. This Community Service Activity aims to improve teachers' abilities in implementing the e-Raport system as a means of reporting grades that is more efficient, accurate, and integrated. The implementation method of the community service is in 3 (three) stages: the preparation stage, the implementation stage, and the evaluation stage. The implementation of the activity was carried out through counseling, training, and direct mentoring methods for 34 teachers and educational staff. During the training, participants were guided from the installation stage, inputting grades, data management, to printing digital report cards. The results of the activity showed a significant increase in teacher understanding and skills, as demonstrated by the participants' ability to prepare report cards independently after the training. In addition to producing changes in the technical aspects of reporting, this activity also had an impact on increasing teacher confidence in utilizing information technology as part of teacher professionalism. The implementation of e-Raport has been proven to accelerate school administration processes while supporting digital transformation in the educational environment.ABSTRAKLatar belakang kegiatan pengabdian ini bahwa pelaporan hasil belajar di SMA Negeri 2 Karawang masih menghadapi kendala akibat proses input nilai yang dilakukan secara manual sehingga membutuhkan waktu lama dan rentan kesalahan. Kondisi ini menghambat efektivitas administrasi akademik serta ketercapaian layanan pendidikan berbasis digital. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan kemampuan guru dalam mengimplementasikan sistem e-Raport sebagai sarana pelaporan nilai yang lebih efisien, akurat, dan terintegrasi. Metode pelaksanaan pengabdian yakni dengan 3 (tiga) tahapan yakni tahap persiapan, tahap pelaksanaan dan tahap evaluasi. Pelaksanaan kegiatan dilakukan melalui metode penyuluhan, pelatihan, dan pendampingan langsung kepada 34 guru dan tenaga pendidik. Selama pelatihan, peserta dibimbing mulai dari tahapan instalasi, input nilai, pengelolaan data, hingga percetakan raport digital. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman dan keterampilan guru, yang ditunjukkan dari kemampuan peserta dalam menyusun rapor secara mandiri setelah pelatihan. Selain menghasilkan perubahan pada aspek teknis pelaporan, kegiatan ini juga berdampak pada meningkatnya kepercayaan diri guru dalam memanfaatkan teknologi informasi sebagai bagian dari profesionalisme pendidik. Implementasi e-Raport terbukti mampu mempercepat proses administrasi sekolah sekaligus mendukung transformasi digital di lingkungan pendidikan.